A Practical Radiosity Method for Predicting Transmission Loss in Urban Environments. Issue 2 (22nd December 2004) - Liang, Ming; Liu, Qin
Abstract : The ability to predict transmission loss or field strength distribution is crucial for determining coverage in planning personal communication systems. This paper presents a practical method to accurately predict entire average transmission loss distribution in complicated urban environments. The method uses a 3D propagation model based on radiosity and a simplified city information database including surfaces of roads and building groups. Narrowband validation measurements with line-of-sight (LOS) and non-line-of-sight (NLOS) cases at 1800 MHz give excellent agreement in urban environments.